2018
DOI: 10.3389/fnins.2018.00559
|View full text |Cite
|
Sign up to set email alerts
|

A Model for a Filling-in Process Triggered by Edges Predicts “Conflicting” Afterimage Effects

Abstract: The goal of our research was to develop a compound computational model that predicts the “opposite” effects of the alternating aftereffects stimuli, such as the “color dove illusion” (Barkan and Spitzer, 2017), and the “filling in the afterimage after the image” (van Lier et al., 2009). The model is based on a filling-in mechanism, through a diffusion equation where the color and intensity of the perceived surface are obtained through a diffusion process of color from the stimulus edges. The model solves the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 58 publications
(211 reference statements)
0
11
0
Order By: Relevance
“…For this purpose, we used a noise mask (Haber and Standing 1970;Felsten and Wasserman 1980), and tested whether abrogating the aftereffect affected the reverse-phi perception. The results presented in Fig 3, demonstrated that the reverse-phi illusion (aftereffect mechanism) was indeed abolished by the noise mask, and therefore, it indicates that the aftereffect, which is resulted by the rebound mechanism (Grossberg 1976;Francis 2010;Zaidi et al 2012;Cohen-Duwek and Spitzer 2018), is essential for perception of the reverse-phi motion.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…For this purpose, we used a noise mask (Haber and Standing 1970;Felsten and Wasserman 1980), and tested whether abrogating the aftereffect affected the reverse-phi perception. The results presented in Fig 3, demonstrated that the reverse-phi illusion (aftereffect mechanism) was indeed abolished by the noise mask, and therefore, it indicates that the aftereffect, which is resulted by the rebound mechanism (Grossberg 1976;Francis 2010;Zaidi et al 2012;Cohen-Duwek and Spitzer 2018), is essential for perception of the reverse-phi motion.…”
Section: Discussionmentioning
confidence: 71%
“…It has been suggested that the mechanism for the aftereffect is the rebound response (Grossberg 1976;Francis 2010;Zaidi et al 2012;Cohen-Duwek and Spitzer 2018). Earlier studies showed that a noise mask can abolish the aftereffect phenomenon (Haber and Standing 1970;Felsten and Wasserman 1980).…”
Section: Psychophysical Experimentsmentioning
confidence: 99%
“…This process is modeled by the Poisson equation. The diffusion process is actually the same mechanism described for the afterimage effect (Cohen-Duwek and Spitzer, 2018).…”
Section: Discussionmentioning
confidence: 72%
“…In addition, we assume that in cases such as the watercolor stimuli, the visual system performs filling-in processes in order to make an “educated guess” and to reconstruct surfaces. (B) Each edge triggers a diffusion process and determines its color (Cohen-Duwek and Spitzer, 2018). (C) The trigger for the diffusion process is determined by the interactions between the gradients of the image, i.e., the gradients between the inner contour (IC) and the outer contour (OC), the gradients between the IC and the background, and between the OC and the background.…”
Section: Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation